A high-strength CO2 corrosion-resistant stainless steel, oil casing and its preparation method and application

By adjusting the composition and process of austenitic stainless steel, a high-strength CO2-resistant stainless steel oil casing was prepared, solving the problem of failure of 300 series austenitic stainless steel in high-concentration CO2 environment, realizing economical and efficient high-temperature and high-pressure application, and possessing excellent corrosion resistance and strength.

CN116179946BActive Publication Date: 2025-02-11ZHEJIANG JIULI HI TECH METALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310048941.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-01
Publication Date
2025-02-11
Estimated Expiration
2043-02-01

AI Technical Summary

Technical Problem

Existing 300 series austenitic stainless steel cannot be effectively used in high-concentration CO2 environments, which makes oil and gas well tubing prone to failure in high-temperature and high-pressure environments, and the high cost of nickel-based alloy materials is not economical.

Method used

By adjusting the composition of 300 series austenitic stainless steel, increasing the nitrogen content and controlling the proportion of other elements, high-strength CO2 corrosion-resistant stainless steel is prepared. Using AOD or AOD+ESR smelting process, combined with hot forging, hot extrusion and cold rolling processes, high-strength CO2 corrosion-resistant stainless steel oil casing is prepared.

Benefits of technology

It enables effective application in oil and gas wells under high temperature, high pressure, and high CO2 content environments, possesses excellent corrosion resistance and high strength, reduces material costs, and is suitable for oil and gas extraction and geothermal resource development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116179946B_ABST
    Figure CN116179946B_ABST
Patent Text Reader

Abstract

The invention relates to the field of stainless steel and its manufacturing, and in particular to a high-strength CO2 corrosion-resistant stainless steel, an oil casing and a preparation method thereof. The stainless steel comprises: C≤0.1%, 0.1%≤Si≤0.5%, 1.5%≤Mn≤5%, 16.5%≤Cr≤25.0%, 8.0%≤Ni≤20.0%, 1.5%≤Mo≤5%, 0.01%≤Al≤0.10%, 0.30%≤Cu≤0.45%, Co≤0.5%, 0.01%≤W≤2.00%, 0.05%≤N≤0.3%, 0.05%≤Re≤0.10%, and the remainder is Fe and other inevitable impurities. The components meet the conditions: Creq / Nieq<2.0, PREN≥25, wherein Nieq is nickel equivalent, Creq is chromium equivalent, and PREN is pitting equivalent. The present invention controls the nitrogen content and adjusts other components, so that the performance of the 300 series austenitic stainless steel in the present invention is greatly improved compared with the existing 300 series austenitic stainless steel, especially the excellent CO2 corrosion resistance and excellent acid fracturing fluid corrosion resistance. The various properties of the material meet the requirements for the development of oil and gas wells in high temperature, high pressure and high CO2 content environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of stainless steel and its manufacturing, in particular to a high-strength CO 2 Anti-corrosion stainless steel, oil casing and its preparation method and application. Background Art

[0002] As the world's demand for oil and gas resources continues to grow, the development of oil and gas fields has gradually moved deeper, and oil and gas wells of 7,600m (25,000 feet) or even deeper have emerged. As an important petroleum equipment material, oil well pipes account for about 60% of the total assets of oil and gas field equipment and 20% to 30% of the cost of well construction. As the depth of wells increases, the service environment of oil well pipes is also becoming increasingly harsh. In the harsh corrosive environment of ultra-deep oil and gas wells, such as high temperature, CO 2 , H 2 S, Cl - Under the combined action of corrosive media such as rust, corrosion and corrosion, the oil and gas well pipe string is very likely to fail. The development of ultra-deep oil and gas resources usually requires the use of oil casing with high strength and high corrosion resistance.

[0003] In order to reduce corrosion, the use of nickel-based alloy materials with excellent corrosion resistance as oil casing has become a better choice, but it also has some disadvantages, such as the high cost of material production. Therefore, it is considered to use a high-strength structural material widely used in industry - austenitic stainless steel. Austenitic stainless steel as oil casing can be the direction of material selection. However, austenitic stainless steel represented by 300 series stainless steel is not particularly excellent in corrosion resistance. For example, when it is required to select materials with better resistance to general corrosion and pitting corrosion, duplex stainless steel is more popular than austenitic stainless steel. In addition, due to the limitation of the strength of austenitic stainless steel materials, 300 series austenitic stainless steel is not currently used as a material for oil casing.

[0004] High temperature, high pressure and high concentration of CO 2 The oil and gas well environment is one of the oil well conditions often encountered in the process of oil and gas extraction. For such downhole conditions, high corrosion-resistant alloys such as duplex stainless steel and nickel-based alloys must generally be used to meet the use requirements. Moreover, not all corrosion-resistant alloys can withstand high concentrations of CO. 2 Therefore, it is relatively cheap to manufacture and can be used in high temperature, high pressure, high concentration of CO 2 It is necessary to use alloy materials in oil well environments. Then, the developed alloy materials will be used as oil casing, which will be of great significance to the development of the national economy. Summary of the invention

[0005] The present invention is to overcome the problem that the 300 series austenitic stainless steel in the prior art cannot be used for high concentration CO 2The oil well environment provides a high strength, high temperature, high pressure and high CO 2 Corrosion-resistant stainless steel, oil casing and its preparation method and application, to achieve 300 series austenitic stainless steel oil casing in high concentration CO 2 Environmental oil well application requirements, so that high-temperature, high-pressure, high-CO content can be prepared efficiently and at low cost 2 Various specifications of oil casing and tubing required by the environment.

[0006] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions:

[0007] A high strength CO resistant 2 The invention discloses a pitting corrosion stainless steel, which comprises, by weight percentage, C≤0.1%, 0.1%≤Si≤0.5%, 1.5%≤Mn≤5%, 16.5%≤Cr≤25.0%, 8.0%≤Ni≤20.0%, 1.5%≤Mo≤5%, 0.01%≤Al≤0.10%, 0.30%≤Cu≤0.45%, Co≤0.5%, 0.01%≤W≤2.00%, 0.05%≤N≤0.3%, 0.05%≤Re≤0.10%, and the balance is Fe and other inevitable impurities, and the composition satisfies the conditions: Creq / Nieq<2.0, PREN≥25, wherein Nieq is nickel equivalent, Creq is chromium equivalent, and PREN is pitting corrosion equivalent.

[0008] Since the corrosion resistance and mechanical properties of 300 series austenitic stainless steel are relatively weak, 300 series austenitic stainless steel is not currently used for oil casing. By improving 300 series austenitic stainless steel, this relatively cheap austenitic stainless steel can be used in high temperature, high pressure and high concentration CO 2 Therefore, a relatively cheap and highly CO2-resistant 2 The 300 series austenitic stainless steel alloy material has excellent corrosion resistance and acid fracturing fluid corrosion resistance, and can be used in specific high temperature, high pressure and high CO 2 The low permeability oil and gas field environment is of great significance to economic development.

[0009] Based on the typical 316L austenitic stainless steel material, the present invention improves and adjusts the composition thereof, and especially increases the nitrogen (N) content in the alloy. By increasing the N content in the alloy material to a certain extent, the strength and corrosion resistance of the material are improved, and N can also inhibit the precipitation of harmful phases such as σ phase. However, since too high N will lead to defects such as pores in the ingot, and may also lead to the precipitation of other harmful phases, the higher the nitrogen content, the better. It is necessary to strictly control the nitrogen content in the alloy.2 The mass percentage of N in the corrosion-resistant stainless steel is controlled to be 0.05% to 0.30%.

[0010] In addition to strictly adjusting and controlling the N content in the alloy material, other components in the alloy are also strictly controlled. The principles of adding other elements in the alloy are as follows:

[0011] Carbon (C) component: The addition of C can effectively improve the strength of the material, but too high a C content can easily cause alloy element carbides to precipitate at the grain boundaries during product manufacturing, resulting in the appearance of local Cr-poor areas at the grain boundaries, which in turn leads to a decrease in the mechanical properties and corrosion resistance of the material. For the technical solution of the present invention, C is a residual element and should be controlled as low as possible. However, controlling the C content to an infinitely low level will greatly increase the production cost. Therefore, the CO resistant 2 The mass percentage of C in the corrosion-resistant stainless steel alloy is set to be less than 0.1%.

[0012] Silicon (Si) component: Si is an effective deoxidizer. In order to improve the strength of the material, a certain amount of Si element needs to be added, but too much Si can easily lead to SiO 2 The formation of non-metallic inclusions such as , causes the material toughness to decrease. In view of this, in the CO 2 In the corrosion-resistant stainless steel alloy, the lower limit of the mass percentage of Si is designed to be 0.1%, and the upper limit thereof is designed to be 0.5%.

[0013] Manganese (Mn) component: Mn is an austenite-forming element that can increase the solubility of N in steel, thereby improving the strength and corrosion resistance of the material. In addition, Mn is also an effective deoxidizer, which can remove S. However, too much Mn will also promote the formation of carbides, thereby reducing the toughness and corrosion resistance of the material. For this reason, CO2-resistant 2 The mass percentage of Mn in the corrosion-resistant stainless steel alloy is set to 1.5% to 5.0%.

[0014] Chromium (Cr) component: Adding Cr can greatly improve the material's resistance to localized corrosion and uniform corrosion, but too much Cr will promote the formation of harmful second phases such as high-temperature ferrite or σ phase. The presence of these second phases will lead to a decrease in the material's resistance to acidification and stress corrosion cracking (SCC). Therefore, it is necessary to increase the CO resistance 2 The mass percentage of Cr in the corrosion-resistant stainless steel alloy is set to 16.5% to 25.0%.

[0015] Nickel (Ni) component: Ni is an austenite-forming element that can improve the material's SCC resistance and local corrosion resistance. However, too high a Ni content will not only reduce the material's work hardening properties, but will also significantly increase the material cost. 2 The mass percentage of Ni in the corrosion-resistant stainless steel alloy is controlled to be 8.0% to 20.0%.

[0016] Molybdenum element (Mo) component: Mo can effectively improve the material in high Cl - The pitting corrosion resistance, crevice corrosion resistance and SCC resistance in the environment. However, Mo is a ferrite forming element. Excessive Mo content will lead to the formation of harmful second phases such as high-temperature ferrite or σ phase of the material. The presence of these second phases will lead to a decrease in the pitting corrosion resistance and SCC resistance of the material. Based on the technical solution of the present invention, the mass percentage of Mo should be controlled to 1.5% to 5.0%.

[0017] Aluminum (Al) component: Al is an effective deoxidizer and an alloying element that is difficult to avoid in the steelmaking process. In the technical solution of the present invention, once the mass percentage of Al exceeds 0.10%, the toughness and hot workability of the material will be destroyed. Therefore, CO resistance 2 The mass percentage of Al in the corrosion-resistant stainless steel alloy needs to be set between 0.01% and 0.10%.

[0018] Copper (Cu) component: Adding Cu to stainless steel helps improve the material's corrosion resistance. In addition, Cu is also an austenite-forming element. However, too high a Cu content will reduce the material's work hardening properties. For this reason, CO resistant 2 The mass percentage of Cu in the corrosion-resistant stainless steel alloy needs to be controlled to 0.30% to 0.45%.

[0019] Cobalt (Co) component: Co can increase the oxidation resistance and corrosion resistance of materials, and can significantly improve the high-temperature mechanical properties of materials. It is an important alloying element for stainless steel, heat-resistant steel, and high-temperature alloys. However, Co is a rare and precious metal and is expensive, so it is not suitable for CO 2 The mass percentage of Co in the corrosion-resistant stainless steel alloy needs to be controlled to be less than 0.5%.

[0020] Tungsten (W) component: The addition of W helps to improve the material's resistance to sulfide stress corrosion cracking. At the same time, W can also effectively improve the material's high-temperature mechanical properties. 2 The mass percentage of W in the corrosion-resistant stainless steel alloy is set to 0.01% to 2.00%.

[0021] Rare earth element component: The addition of Re can effectively improve the toughness of the material. For the technical solution of the present invention, when the mass percentage of the rare earth element Re exceeds 0.10%, the welding performance of the material will be reduced. 2 In the corrosion-resistant stainless steel alloy, the mass percentage of the rare earth element Re is controlled in the range of 0.05% to 0.10%.

[0022] In addition, since the inevitable impurity elements in stainless steel are mainly P and S, these two impurity elements need to be controlled as low as possible.

[0023] Preferably, the high strength CO resistant 2 The corrosion stainless steel composition also meets the conditions: Creq / Nieq<2.0, PREN≥25, where Nieq is nickel equivalent, Creq is chromium equivalent, and PREN is pitting equivalent. The calculation formulas of Nieq, Creq, and PREN are:

[0024] ①Nieq=Ni+Co+0.1Mn-0.01Mn 2 +18N+30C

[0025] ②Creq=Cr+1.5Mo+1.5W+0.48Si+2.3V+1.75Nb+2.5Al

[0026] ③PREN=Cr+3.3×(Mo+0.5W)+16×N

[0027] Nickel equivalent is an indicator of the degree of austenitization of stainless steel weld metal structure, and chromium equivalent is an indicator of the degree of ferritization of weld metal structure. The possibility and relative content of ferrite formation in austenitic stainless steel can be qualitatively estimated by chromium-nickel equivalent. Due to the differences in chemical composition, mechanical properties and thermal stability between ferrite and austenite matrix, the appearance of ferrite will have an adverse effect on the performance of austenitic stainless steel in some cases. Therefore, the content of ferrite can be estimated by Creq / Nieq to control the appearance of ferrite. Since ferrite is a major component of CO resistance, it is important to consider the relative content of ferrite in the weld metal structure. 2 Nieq is a harmful phase in stainless steel alloys, so its content should be controlled as low as possible. Here, the component content in the alloy is designed to meet Creq / Nieq<2.0.

[0028] PREN is a set of algorithms based on the mass fraction of certain elements in metals. It is an important parameter used to quantitatively evaluate and indicate the comprehensive corrosion resistance of stainless steel. Metals with higher PREN values ​​are more resistant to local corrosion than metals with lower PREN values. The value calculated by this formula basically shows the relative resistance to pitting corrosion. Here, the content of the components in the alloy is designed to meet PREN ≥ 25.

[0029] Preferably, the stainless steel composition further comprises at least one of the following in weight percentage: 0<Nb≤0.1%, 0<V≤0.1%, 0<Ti≤0.1%.

[0030] Nb, V, Ti have a strong binding ability with C and N. Nb, V, Ti can form respective carbides, nitrides or carbonitrides with C and N. Such compounds help to improve the mechanical properties of the material. In addition, Ti can also enhance the corrosion resistance of the material. However, with regard to the technical solution of the present invention, once the mass percentage of one of Nb, V, and Ti exceeds 0.1%, the particles of the precipitated phase will be coarse, and the non-metallic inclusions in the material will increase, which will in turn destroy the strength of the material; at the same time, it will also reduce the welding performance of the material. Therefore, the mass percentage of Nb, V, and Ti in the stainless steel corrosion-resistant alloy described in the present invention shall not exceed 0.1%.

[0031] A high strength CO resistant 2 The method for preparing the corrosion-resistant stainless steel oil casing comprises the following steps:

[0032] (1) Smelting: According to the high strength CO2 resistance described above 2 The formula of corrosion-resistant stainless steel is to use AOD or AOD+ESR smelting process to smelt molten steel;

[0033] (2) making a tube blank: subjecting the molten steel obtained in step (1) to die casting, followed by hot forging to obtain a tube blank for extrusion, or subjecting the molten steel obtained in step (1) to continuous casting, followed by hot rolling to obtain a tube blank for perforation;

[0034] (3) Heating pipe making: hot extrusion or hot perforation treatment is performed on the tube blank in step (2) to make a seamless rough tube;

[0035] (4) Heat treatment: subjecting the rough pipe in step (3) to solid solution heat treatment to obtain a rough pipe in a solid solution state extruded or perforated state;

[0036] (5) Cold rolling: The solid solution extruded or perforated rough pipe in step (4) is cold-rolled to form a pipe with required specifications and strength.

[0037] The corrosion-resistant stainless steel alloy in the present invention, its alloy composition design, especially the N element content, has a great influence on the mechanical properties and corrosion resistance of the final product. Therefore, the present invention recommends a raw material smelting process, and recommends the use of a non-vacuum smelting process to smelt the raw materials. The AOD / VOD process can be used to smelt the raw materials to ensure the N element content of the raw materials. In order to further improve the purity of the product and improve the corrosion resistance of the product, the ESR remelting process can be further used to perform secondary smelting on the raw materials after the AOD / VOD smelting process is completed to improve the overall quality of the raw materials.

[0038] Preferably, in step (2), the forging ratio during the hot forging process is not less than 3.0.

[0039] In the present invention, the forging ratio is limited to a range of not less than 3.0 during the hot forging process, which can make the elements inside the forged round steel more evenly distributed, and the grain structure more evenly distributed, thereby improving the corrosion resistance and mechanical properties of the corrosion-resistant stainless steel alloy material. When the forging ratio is less than 3.0, the distribution of the elements and the grain structure will be unevenly dispersed, which will cause the corrosion resistance and mechanical properties to decrease to varying degrees.

[0040] Preferably, the extrusion or perforation temperature during the hot extrusion or hot perforation treatment in step (3) is 1150-1200°C.

[0041] The extrusion or perforation temperature in the hot extrusion or hot perforation process of the present invention is 1150-1200°C, which is higher than the recrystallization temperature of the round steel tube billet. Within this temperature range, the deformation resistance of the round steel is greatly reduced and it is easier to shape. When the extrusion or perforation temperature is lower than 1150°C, the material has a large resistance to thermal deformation, and the perforator or extruder is prone to suffocation or pipe cracking. When the extrusion or perforation temperature is greater than 1200°C, although the material's resistance to thermal deformation is reduced, the material's plasticity is also greatly reduced, and the pipe is prone to cracking. At the same time, after extrusion or perforation, the material's grains are severely broken and the grains are fully refined, so that a microstructure with uniform material properties can be obtained.

[0042] Preferably, in step (3), when hot extrusion or hot piercing is performed, the tube blank is first preheated to 850-900°C for 1-2 hours to completely austenitize the alloy, and then heated to the extrusion or piercing temperature.

[0043] Preheating before hot extrusion or hot piercing can soften the tube, improve its shaping, and reduce the requirements for molds and equipment.

[0044] Preferably, the solution heat treatment temperature in step (4) is 980-1200°C.

[0045] Preferably, the single reduction amount during the cold rolling process in step (5) is 10 to 60%.

[0046] The cold deformation process in the present invention is a key step to ensure the dimensional accuracy and mechanical properties of the material. The single deformation amount can vary between 10 and 60%, and the final cold deformation amount can be optimized according to the mechanical property requirements of the final product. A large cold deformation amount is preferred in the intermediate process to refine and homogenize the grain structure. The intermediate heat treatment temperature is 980 to 1200°C, which is the same as the material solution treatment temperature, so that the microstructure in the stainless steel oil casing is transformed into a single solid solution austenite structure and the residual stress formed in the previous cold working process is eliminated, so as to prepare the organization for the next cold deformation. After the cold rolling treatment, the obtained pipe needs to be finished.

[0047] A high strength CO resistant 2 The corrosion-resistant stainless steel oil casing is prepared by the method.

[0048] The oil casing has excellent corrosion resistance, especially anti-CO 2 It has good corrosion resistance and acid fracturing fluid corrosion resistance, and has high strength and a wide strength range of 52KSI to 135KSI.

[0049] A high strength CO resistant 2 The application of corrosion-resistant stainless steel oil casing in the fields of oil and natural gas extraction, as well as geothermal resource development and other high-temperature fields.

[0050] The present invention has the following beneficial effects:

[0051] (1) The stainless steel alloy of the present invention has high strength, a uniform austenite structure inside, and a very small amount of non-metallic inclusions and other second phases. Compared with the martensitic stainless steel in the prior art, the stainless steel alloy with austenite microstructure has the characteristics of high strength and controllable strength through deformation strengthening, and can achieve different strengths through the control of the subsequent cold rolling process to meet different strength requirements;

[0052] (2) The present invention controls the nitrogen content and adjusts other components to make the 300 series stainless steel with austenite microstructure also have excellent corrosion resistance, especially excellent CO resistance. 2 Corrosion resistance and excellent resistance to acid fracturing fluid corrosion;

[0053] (3) The stainless steel oil casing prepared by the present invention has good surface quality, high strength and CO resistance. 2 Good corrosion resistance, excellent resistance to acid fracturing fluid corrosion and good welding performance. The material's various properties meet the requirements of high temperature, high pressure and high CO 2Environmental oil and gas well development requirements, suitable for use in the fields of oil and natural gas extraction, as well as high-temperature fields such as geothermal resource development. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a microstructure (high magnification) photograph of Example 1 of the present invention.

[0055] Figure 2 This is a microstructure (low magnification) photograph of Example 1 of the present invention. DETAILED DESCRIPTION

[0056] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0057] Example 1

[0058] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 3.0. The diameter of the round steel after forging is 241 mm, and its composition is shown in Table 1. The Creq / Nieq of the alloy is 1.5, and the PREN is 26.5.

[0059] Table 1 Chemical composition of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0060] C Mn P S Si Ni Cr Mo Ti 0.012 1.62 0.11 0.0025 0.22 12.16 17.3 2.42 / N Cu V Co B Nb W Al Ce(Re) 0.076 0.022 / 0.024 0.0003 0.007 0.013 0.012 0.013 .

[0061] The round steel with a diameter of 241mm and a length of 8m was cut into 45cm extrusion billets, and the extruded billets were drilled, end chamfered, inspected and ground, degreased and cleaned, and then preheated at 850℃ in a ring heating furnace for 1.5 hours, and then heated to 1170℃ in a primary induction heating furnace, and then expanded, and then induction heated to 1180℃ for the second time, and finally extruded on a 4200t hot extrusion machine with an extrusion ratio of 4.1 and a hot extrusion temperature of 1180℃, to obtain a Φ152*20mm rough pipe with good surface quality, uniform surface and no obvious defects, and then the rough pipe was solution heat treated at 1040℃.

[0062] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ152*20mm to Φ114*13mm, with a cold deformation of 50.27%. It is degreased and annealed at a temperature of 1040℃ for 25 minutes, pickled and straightened.

[0063] Then the intermediate quality pipes are subjected to final cold rolling, and the pipe specifications are rolled from Φ114*13mm to Φ88.9*7.34mm, with a cold deformation of 54.41%. After finishing, 125KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0064] The stainless steel oil casing in Example 1 was examined by scanning electron microscopy, and the structure of the pipe is shown in the following figure: Figure 1 and Figure 2 shown.

[0065] Figure 1 , Figure 2 The metallographic structure of Example 1 of the present invention is shown. As can be seen from the figure, its microstructure is a uniform and fine austenite structure, with almost no σ phase and other harmful phases.

[0066] Example 2

[0067] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 4.0. The diameter of the round steel after forging is 255 mm, and its composition is shown in Table 2. The Creq / Nieq of the alloy is 1.7, and the PREN is 26.5.

[0068] Table 2 Chemical composition of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0069] C Mn P S Si Ni Cr Mo Ti 0.033 2.12 0.12 0.0036 0.11 11.13 20.1 1.52 / N Cu V Co B Nb W Al Y(Re) 0.068 0.45 / 0.027 0.0002 0.006 0.17 0.031 0.015 .

[0070] The round steel with a diameter of 255mm and a length of 8m was cut into 45cm extrusion billets, and the extruded billets were drilled, end chamfered, inspected and ground, degreased and cleaned, and then preheated at 900℃ in a ring heating furnace for 1 hour, and then heated to 1170℃ in a primary induction heating furnace, and then expanded, and then subjected to secondary induction heating to 1180℃, and finally extruded on a 4200t hot extrusion machine with an extrusion ratio of 4.3 and a hot extrusion temperature of 1180℃, to obtain a Φ152*25mm rough pipe with good surface quality, uniform surface and no obvious defects, and then the rough pipe was solution heat treated at 1040℃.

[0071] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ152*25mm to Φ127*15mm, with a cold deformation of 47.09%. It is degreased and annealed at a temperature of 1040℃ for 25 minutes, pickled and straightened.

[0072] Then the intermediate quality pipes are subjected to final cold rolling, and the pipe specifications are rolled from Φ127*15mm to Φ88.9*7.34mm, with a cold deformation of 64.37%. After finishing, 115KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0073] Example 3

[0074] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 5.0. The diameter of the round steel after forging is 241 mm, and its composition is shown in Table 3. The Creq / Nieq of the alloy is 1.1, and the PREN is 25.6.

[0075] Table 3 Chemical composition of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0076] C Mn P S Si Ni Cr Mo Ti 0.045 1.51 0.09 0.0045 0.37 17.6 19.8 1.51 / N Cu V Co B Nb W Al Ce(Re) 0.051 0.37 / 0.31 0.0003 0.097 0.015 0.052 0.082 .

[0077] The round steel with a diameter of 241mm and a length of 8m was cut into 45cm extrusion billets, and the extruded billets were drilled, end chamfered, inspected and ground, degreased and cleaned, and then preheated at 850℃ in a ring heating furnace for 1.2 hours, and then heated to 1130℃ in a primary induction heating furnace, and then expanded, and then induction heated to 1150℃ for the second time, and finally extruded on a 4200t hot extrusion machine with an extrusion ratio of 4.1 and a hot extrusion temperature of 1150℃, to obtain a Φ152*20mm rough pipe with good surface quality, uniform surface and no obvious defects, and then the rough pipe was solution heat treated at 980℃.

[0078] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ152*20mm to Φ114*13mm, with a cold deformation of 50.27%. It is degreased and annealed at 980℃ for 25 minutes, pickled and straightened.

[0079] Then the intermediate quality pipes are subjected to final cold rolling, and the pipe specifications are rolled from Φ114*13mm to Φ88.9*7.34mm, with a cold deformation of 54.41%. After finishing, 115KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0080] Example 4

[0081] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 6.0. The diameter of the round steel after forging is 241 mm, and its composition is shown in Table 4. The Creq / Nieq of the alloy is 0.9, and the PREN is 25.7.

[0082] Table 4 Chemical composition of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0083] C Mn P S Si Ni Cr Mo Ti 0.031 3.11 0.08 0.0032 0.49 19.2 16.2 2.5 / N Cu V Co B Nb W Al Ce(Re) 0.074 0.41 0.021 0.5 0.0005 / 0.021 0.011 0.081 .

[0084] The round steel with a diameter of 241mm and a length of 8m was cut into 45cm perforated billets. The perforated billets were drilled with positioning holes, inspected, ground, degreased and cleaned, and then heated at 1180℃ in an inclined bottom heating furnace for 2 hours. Subsequently, the billet was obliquely rolled and perforated with a rolling ratio of 3.1 to obtain a Φ255*20mm rough pipe with good surface quality, uniform surface and no obvious defects. The rough pipe was then solution heat treated at 1200℃.

[0085] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ255*20mm to Φ215*15mm, with a cold deformation of 36.17%. It is degreased and annealed at a temperature of 1200℃ for 25 minutes, pickled and straightened.

[0086] Then the intermediate quality pipes are subjected to final cold rolling, and the pipe specifications are rolled from Φ215*15mm to Φ178*10.36mm, with a cold deformation of 42.11%. After finishing, 115KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0087] Example 5

[0088] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 4.0. The diameter of the round steel after forging is 255 mm, and its composition is shown in Table 5. The Creq / Nieq of the alloy is 1.8, and the PREN is 28.9.

[0089] Table 5 Chemical composition of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0090] C Mn P S Si Ni Cr Mo Ti 0.051 2.79 0.15 0.0029 0.32 10.1 17.1 2.31 / N Cu V Co B Nb W Al Y(Re) 0.053 0.35 0.035 0.25 0.0004 / 1.99 0.077 0.05 .

[0091] The round steel with a diameter of 255mm and a length of 7m was cut into 40cm extrusion billets, and the extruded billets were drilled, end chamfered, inspected and ground, degreased and cleaned, and then preheated at 890℃ in a ring heating furnace for 1.2 hours, and then heated to 1150℃ in an induction heating furnace, and then expanded, and then induction heated to 1180℃ for the second time, and finally extruded on a 4200t hot extrusion machine with an extrusion ratio of 4.3 and a hot extrusion temperature of 1180℃, to obtain a Φ152*25mm rough pipe with good surface quality, uniform surface and no obvious defects, and then the rough pipe was solution heat treated at 990℃.

[0092] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ152*25mm to Φ127*15mm, with a cold deformation of 47.09%. It is degreased and annealed at 990℃ for 25 minutes, pickled and straightened.

[0093] Then the second pass of cold rolling is performed on the intermediate quality pipe, and the pipe specification is rolled from Φ127*15mm to Φ92*8mm, with a cold deformation of 60.00%. Then it is degreased and annealed at 990℃ for 25 minutes, pickled and straightened.

[0094] The processed rough pipe is cold drawn in the final pass, and the pipe specification is cold drawn from Φ92*8mm to Φ88.9*7.34mm, with a cold deformation of 10.92%. Then it is degreased and annealed at 990℃ for 25 minutes, pickled and straightened. After finishing, 52KSI high strength and CO resistant steel is obtained. 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0095] Example 6

[0096] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 5.0. The diameter of the round steel after forging is 241 mm, and its composition is shown in Table 6. The Creq / Nieq of the alloy is 1.2, and the PREN is 42.0.

[0097] Table 6 Chemical composition of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0098] C Mn P S Si Ni Cr Mo Ti 0.067 4.1 0.13 0.0041 0.49 19.7 23.5 3.82 / N Cu V Co B Nb W Al Ce(Re) 0.27 0.30 0.098 0.42 0.0006 / 0.93 0.097 0.074 .

[0099] The round steel with a diameter of 241mm and a length of 7m was cut into 40cm extrusion billets, and the extruded billets were drilled, end chamfered, inspected and ground, degreased and cleaned, and then preheated at 850℃ in a ring heating furnace for 1.5 hours, and then heated to 1140℃ in an induction heating furnace, and then expanded, and then induction heated to 1150℃ for the second time, and finally extruded on a 4200t hot extrusion machine with an extrusion ratio of 4.1 and a hot extrusion temperature of 1150℃, to obtain a Φ152*20mm rough pipe with good surface quality, uniform surface and no obvious defects, and then the rough pipe was solution heat treated at 1100℃.

[0100] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ152*20mm to Φ114*13mm, with a cold deformation of 50.27%. It is degreased and annealed at a temperature of 1100℃ for 25 minutes, pickled and straightened.

[0101] Then the intermediate quality pipes are subjected to final cold rolling, and the pipe specifications are rolled from Φ114*13mm to Φ88.9*7.34mm, with a cold deformation of 54.41%. After finishing, 110KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0102] Example 7

[0103] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 5.0. The diameter of the round steel after forging is 255 mm, and its composition is shown in Table 7. The Creq / Nieq of the alloy is 1.3, and the PREN is 40.0.

[0104] Table 7 Chemical composition of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0105] C Mn P S Si Ni Cr Mo Ti 0.01 3.72 0.09 0.0037 0.36 20.0 24.1 4.11 0.003 N Cu V Co B Nb W Al Ce(Re) 0.14 0.33 / 0.025 0.0006 / 0.01 0.081 0.092 .

[0106] The round steel with a diameter of 255mm and a length of 6m was cut into 45cm extrusion billets, and the extruded billets were drilled, chamfered, inspected and ground, degreased and cleaned, and then preheated at 860℃ in a ring heating furnace for 1.5 hours, and then heated to 1120℃ in an induction heating furnace, and then expanded, and then induction heated to 1160℃ for the second time, and finally extruded on a 4200t hot extrusion machine with an extrusion ratio of 4.3 and a hot extrusion temperature of 1160℃, to obtain a Φ152*25mm rough pipe with good surface quality, uniform surface and no obvious defects, and then the rough pipe was solution heat treated at 1120℃.

[0107] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ152*25mm to Φ127*15mm, with a cold deformation of 47.09%. It is degreased and annealed at a temperature of 1120℃ for 25 minutes, pickled and straightened.

[0108] Then the intermediate quality pipes are cold rolled to reduce the pipe size from Φ127*15mm to Φ88.9*7.34mm, with a cold deformation of 64.37%. After finishing, 135KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0109] Example 8

[0110] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 6.0. The diameter of the round steel after forging is 263 mm, and its composition is shown in Table 8. The Creq / Nieq of the alloy is 1.2, and the PREN is 37.6.

[0111] Table 8 Chemical composition of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0112] C Mn P S Si Ni Cr Mo Ti 0.034 5.0 0.11 0.0039 0.46 16.5 21.8 2.78 0.042 N Cu V Co B Nb W Al Y(Re) 0.29 0.37 / 0.29 0.0008 / 1.23 0.058 0.076 .

[0113] The round steel with a diameter of 263mm and a length of 6m was cut into 40cm perforated billets. The perforated billets were drilled with positioning holes, inspected, ground, degreased and cleaned, and then heated at 1180℃ in an inclined bottom heating furnace for 2 hours. Subsequently, the billet was obliquely rolled and perforated with a rolling ratio of 2.0 to obtain a Φ280*35mm rough pipe with good surface quality, uniform surface and no obvious defects. The rough pipe was then solution heat treated at 1060℃.

[0114] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ280*35mm to Φ250*30mm, with a cold deformation of 23.03%. It is degreased and annealed at a temperature of 1060℃ for 25 minutes, pickled and straightened.

[0115] Then the intermediate quality pipes are subjected to final cold rolling, and the pipe specifications are rolled from Φ250*30mm to Φ199.9*25.4mm, with a cold deformation of 32.84%. After finishing, 120KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0116] Example 9

[0117] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 3.0. The diameter of the round steel after forging is 255 mm, and its composition is shown in Table 9. The Creq / Nieq of the alloy is 1.4, and the PREN is 43.2.

[0118] Table 9 Chemical compositions of stainless steel alloys (mass fraction%, the remainder being Fe and other unavoidable impurities)

[0119] C Mn P S Si Ni Cr Mo Ti 0.076 4.72 0.13 0.0027 0.18 18.8 24.9 4.32 0.1 N Cu V Co B Nb W Al Ce(Re) 0.16 0.33 / 0.14 0.0007 / 0.87 0.091 0.098 .

[0120] The round steel with a diameter of 255mm and a length of 8m was cut into 40cm extrusion billets, and the extruded billets were drilled, end chamfered, inspected and ground, degreased and cleaned, and then preheated at 900℃ in a ring heating furnace for 1 hour, and then heated to 1160℃ in a primary induction heating furnace, and then expanded, and then induction heated to 1180℃ for the second time, and finally extruded on a 4200t hot extrusion machine with an extrusion ratio of 4.3 and a hot extrusion temperature of 1180℃, to obtain a Φ152*25mm rough pipe with good surface quality, uniform surface and no obvious defects, and then the rough pipe was solution heat treated at 1000℃.

[0121] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ152*25mm to Φ127*15mm, with a cold deformation of 47.09%. It is degreased and annealed at a temperature of 1000℃ for 25 minutes, pickled and straightened.

[0122] Then the intermediate quality pipes are cold rolled to reduce the pipe size from Φ127*15mm to Φ88.9*7.34mm, with a cold deformation of 64.37%. After finishing, 135KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0123] Example 10

[0124] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 4.0. The diameter of the round steel after forging is 302 mm, and its composition is shown in Table 10. The Creq / Nieq of the alloy is 1.5, and the PREN is 39.1.

[0125] Table 10 Chemical compositions of stainless steel alloys (mass fraction%, the remainder being Fe and other unavoidable impurities)

[0126] C Mn P S Si Ni Cr Mo Ti 0.049 1.81 0.11 0.0034 0.33 15.3 18.2 5.0 / N Cu V Co B Nb W Al Y(Re) 0.12 0.42 0.044 0.35 0.0007 / 1.52 0.072 0.067 .

[0127] The round steel with a diameter of 302mm and a length of 6m was cut into 45cm perforated billets. The perforated billets were drilled with positioning holes, inspected, ground, degreased and cleaned, and then heated at 1180℃ in an inclined bottom heating furnace for 2 hours. Subsequently, the billet was obliquely rolled and perforated with a rolling ratio of 2.0 to obtain a Φ355*35mm rough pipe with good surface quality, uniform surface and no obvious defects. The rough pipe was then solution heat treated at 1190℃.

[0128] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ355*35mm to Φ310*25mm, with a cold deformation of 36.38%. It is degreased and annealed at a temperature of 1190℃ for 25 minutes, pickled and straightened.

[0129] Then the intermediate quality pipes are subjected to final cold rolling, and the pipe specifications are rolled from Φ310*25mm to Φ273*14mm, with a cold deformation of 49.11%. After finishing, 125KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0130] Embodiment 11

[0131] The AOD process is used to smelt the tube billet (i.e. round steel), which is then continuously cast, hot-rolled and polished for delivery. The bar diameter is 302 mm and its composition is shown in Table 11. The Creq / Nieq of the alloy is 1.2 and the PREN is 28.3.

[0132] Table 11 Chemical compositions of stainless steel alloys (mass fraction%, the remainder being Fe and other unavoidable impurities)

[0133] C Mn P S Si Ni Cr Mo Ti 0.017 1.6 0.018 0.002 0.22 14.9 17.5 2.71 / N Cu V Co B Nb W Al Y(Re) 0.11 0.33 / 0.28 0.0005 0.009 0.041 0.0029 0.071 .

[0134] The round steel with a diameter of 302mm and a length of 6m was cut into 45cm perforated billets. The perforated billets were drilled with positioning holes, inspected, ground, degreased and cleaned, and then heated at 1180℃ in an inclined bottom heating furnace for 2 hours. Subsequently, the billet was obliquely rolled and perforated with a rolling ratio of 2.0 to obtain a Φ355*35mm rough pipe with good surface quality, uniform surface and no obvious defects. The rough pipe was then solution heat treated at 1190℃.

[0135] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ355*35mm to Φ310*25mm, with a cold deformation of 36.38%. It is degreased and annealed at a temperature of 1190℃ for 25 minutes, pickled and straightened.

[0136] Then the intermediate quality pipes are subjected to final cold rolling, and the pipe specifications are rolled from Φ310*25mm to Φ273*14mm, with a cold deformation of 49.11%. After finishing, 120KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0137]

Performance test and test results

[0138] The high strength CO resistant 2 The corrosion-resistant stainless steel alloy seamless oil casing was sampled and tested for mechanical properties. The test results are shown in Tables 12 to 14 respectively.

[0139] Table 12 Room temperature tensile properties of Examples 1 to 11

[0140] Serial number Temperature / ℃ <![CDATA[R m / MPa]]> <![CDATA[R p0.2 / MPa]]> A / % 1 25 985 875 20 2 25 924 796 19 3 25 942 823 22 4 25 956 825 23 5(solid solution state) 25 566 376 31 6 25 932 778 23 7 25 1078 955 19 8 25 963 843 20 9 25 1063 962 18 10 25 993 892 20 11 25 946 853 19 .

[0141] Table 13 Hardness test of Examples 1 to 11 (HRC)

[0142] Serial number Single value 1 Single value 2 Single value 3 average value 1 26.6 28.2 28.3 27.7 2 27.2 27.9 28.1 27.7 3 28.3 28.5 28.4 28.4 4 28.6 28.3 28.5 28.5 5(solid solution state) 21.3 22.4 21.7 21.8 6 27.9 28.3 28.7 28.3 7 31.2 31.1 30.6 31.0 8 28.6 28.3 28.5 28.5 9 30.9 31.3 31.4 31.2 10 29.1 28.9 29.4 29.1 11 27.6 27.9 28.3 27.9 .

[0143] Table 14 Low temperature impact properties (KV8, J) of Examples 1 to 11

[0144] Serial number Sample size mm Test temperature ℃ Single value 1 Single value 2 Single value 3 average value 1 10*10*55 -10 248.26 251.74 254.59 251.53 2 10*10*55 -10 246.34 248.92 247.87 247.71 3 10*10*55 -10 256.67 258.32 258.91 257.97 4 10*10*55 -10 261.62 259.23 264.78 261.88 5(solid solution state) 10*10*55 -10 293.46 295.87 296.39 295.24 6 10*10*55 -10 253.58 254.59 253.42 253.86 7 10*10*55 -10 229.67 227.72 234.03 230.47 8 10*10*55 -10 245.86 251.63 248.74 248.74 9 10*10*55 -10 234.74 232.19 229.94 232.29 10 10*10*55 -10 249.56 256.49 253.45 253.17 11 10*10*55 -10 228.57 232.9 234.14 231.88 .

[0145] The high strength CO resistant 2 Sampling of stainless steel alloy seamless oil casing and CO2 resistance using weight loss method 2 Corrosion performance test, detailed test conditions and solution medium composition are shown in Table 15, and the test results are listed in Table 17; the high-strength CO resistant 2 The corrosion resistance of the stainless steel alloy seamless oil casing was tested by weight loss method. The detailed test conditions and solution medium composition are shown in Table 16, and the test results are listed in Table 17.

[0146] Table 15 Anti-CO of Examples 1 to 11 2 Corrosion performance test conditions

[0147]

[0148] Table 16 Test conditions for corrosion resistance of acid fracturing fluids in Examples 1 to 11

[0149] Medium (fresh acid) 10% HCl+1.5% HF+3% HAc+5.1% high temperature acidification corrosion inhibitor Temperature(℃) 140 Dosage <![CDATA[≥20ml / cm 2 ]]> Test time (h) 6 Total pressure(MPa) 10 .

[0150] Table 17 Corrosion resistance of Examples 1 to 11

[0151] Serial number <![CDATA[Simulated CO 2 Corrosion rate (mm / a) under corrosive medium]]> Corrosion rate in simulated acid fracturing corrosive medium (mm / a) 1 0.0051 6.9764 2 0.0051 7.1208 3 0.0049 6.9371 4 0.0052 7.0973 5 0.0049 6.9298 6 0.0039 5.6834 7 0.0041 6.3402 8 0.0042 6.4529 9 0.0037 5.5974 10 0.0041 6.1974 11 0.0052 7.1432 .

[0152] Comparative Example 1

[0153] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 3.0. The diameter of the round steel after forging is 241 mm, and its composition is shown in Table 18. The Creq / Nieq of the alloy is 1.7, and the PREN is 25.2.

[0154] Table 18 Chemical composition of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0155] C Mn P S Si Ni Cr Mo Ti 0.015 2.13 0.12 0.0025 0.35 11.81 18.7 1.83 0 N Cu V Co B Nb W Al Re 0.032 0.37 0 0.25 0.0003 0.045 0.19 0.052 0.061 .

[0156] The round steel with a diameter of 241mm and a length of 8m was cut into 45cm extrusion billets, and the extruded billets were drilled, end chamfered, inspected and ground, degreased and cleaned, and then preheated at 850℃ in a ring heating furnace for 1.5 hours, and then heated to 1170℃ in a primary induction heating furnace, and then expanded, and then induction heated to 1180℃ for the second time, and finally extruded on a 4200t hot extrusion machine with an extrusion ratio of 4.1 and a hot extrusion temperature of 1180℃, to obtain a Φ152*20mm rough pipe with good surface quality, uniform surface and no obvious defects, and then the rough pipe was solution heat treated at 1040℃.

[0157] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ152*20mm to Φ114*13mm, with a cold deformation of 50.27%. It is degreased and annealed at a temperature of 1040℃ for 25 minutes, pickled and straightened.

[0158] Then the intermediate quality pipes are cold rolled to reduce the pipe size from Φ114*13mm to Φ88.9*7.34mm, with a cold deformation of 54.41%. After finishing, 105KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0159] Comparative Example 2

[0160] The AOD+ESR process is used to smelt the tube billet (i.e. round steel), and the steel is delivered after hot forging and polishing, with a forging ratio of 3.0. The diameter of the round steel after forging is 241 mm, and its composition is shown in Table 19. The Creq / Nieq of the alloy is 1.0, and the PREN is 32.5.

[0161] Table 19 Chemical composition of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0162] C Mn P S Si Ni Cr Mo Ti 0.017 1.93 0.11 0.0042 0.22 12.13 17.5 1.83 0 N Cu V Co B Nb W Al Re 0.51 0.41 0 0.16 0.0007 0.034 0.46 0.058 0.059 .

[0163] The round steel with a diameter of 241mm and a length of 8m was cut into 45cm extrusion billets, and the extruded billets were drilled, end chamfered, inspected and ground, degreased and cleaned, and then preheated at 850℃ in a ring heating furnace for 1.5 hours, and then heated to 1170℃ in a primary induction heating furnace, and then expanded, and then induction heated to 1180℃ for the second time, and finally extruded on a 4200t hot extrusion machine with an extrusion ratio of 4.1 and a hot extrusion temperature of 1180℃, to obtain a Φ152*20mm rough pipe with good surface quality, uniform surface and no obvious defects, and then the rough pipe was solution heat treated at 1040℃.

[0164] The processed rough pipe is cold rolled, and the pipe specification is rolled from Φ152*20mm to Φ114*13mm, with a cold deformation of 50.27%. It is degreased and annealed at a temperature of 1040℃ for 25 minutes, pickled and straightened.

[0165] Then the intermediate quality pipes are subjected to final cold rolling, and the pipe specifications are rolled from Φ114*13mm to Φ88.9*7.34mm, with a cold deformation of 54.41%. After finishing, 140KSI high strength and CO resistant 2 Corrosion-resistant stainless steel alloy seamless oil casing.

[0166] Comparative Example 3

[0167] In this comparative example, martensitic stainless steel is used to make the oil casing, and its composition is shown in Table 20.

[0168] Table 20 Chemical components of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0169] C Mn P S Si Ni Cr Mo Ti 0.015 0.41 0.0115 0.0031 0.35 5.04 12.51 1.71 0.0251 N Cu V Co B Nb W Al Re 0.0544 0.0559 0.0593 / / / / / / .

[0170] Comparative Example 4

[0171] In this comparative example, duplex stainless steel is used to make the oil casing, and its composition is shown in Table 21.

[0172] Table 21 Chemical components of stainless steel alloys (mass fraction%, the balance is Fe and other unavoidable impurities)

[0173] C Mn P S Si Ni Cr Mo Ti 0.015 0.668 0.0238 0.001 0.45 5.45 22.38 3.42 / N Cu V Co B Nb W Al Re 0.187 / / / / / / / / .

[0174] Comparative Example 5

[0175] This comparative example uses 15Cr martensitic stainless steel with strong corrosion resistance to make the oil casing, and its composition is shown in Table 22.

[0176] Table 22 Chemical components of alloys (mass percentage, the balance is Fe and other unavoidable impurities)

[0177] C Mn P S Si Ni Cr Mo Ti 0.24 0.18 0.013 0.004 0.28 6.11 14.22 1.83 / N Cu V Co B Nb W Al Re / 0.4 / / / / / / / .

[0178]

Performance test and test results

[0179] The alloy oil casings prepared in Comparative Examples 1 to 5 were sampled and tested for mechanical properties, and the test results are shown in Tables 23 to 25, respectively.

[0180] Table 23 Room temperature tensile properties of comparative examples 1 to 5

[0181] Serial number Temperature / ℃ <![CDATA[R m / MPa]]> <![CDATA[R p0.2 / MPa]]> A / % 1 25 873 739 22 2 25 1077 982 19 3 25 945 876 20 4 25 1055 847 19 5 25 824 692 21 .

[0182] Table 24 Hardness test of comparative examples 1 to 5 (HRC)

[0183] Serial number Single value 1 Single value 2 Single value 3 average value 1 26.6 27.3 26.9 26.9 2 30.2 30.9 31.1 30.7 3 25.2 25.9 28.1 26.5 4 27.4 26.3 27.8 27.0 5 23.8 23.8 24.5 24.0 .

[0184] Table 25 Low temperature impact properties (KV8, J) of comparative examples 1 to 5

[0185] Serial number Sample size mm Test temperature ℃ Single value 1 Single value 2 Single value 3 average value 1 10*10*55 -10 258.62 261.37 267.07 262.35 2 10*10*55 -10 231.32 232.97 228.26 230.85 3 10*10*55 -10 158.85 155.65 157.04 157.18 4 10*10*55 -10 91.65 116.07 107.58 105.1 5 10*10*55 -10 167.32 171.23 174.59 171.05 .

[0186] The alloy oil casing samples prepared in Comparative Examples 1 to 5 were sampled and subjected to CO resistance test using the weight loss method. 2 Corrosion performance test, detailed test conditions and solution medium composition are shown in Table 26, and the test results are listed in Table 28; the alloy oil casing samples prepared in Comparative Examples 1 to 5 were taken, and the anti-acidification liquid corrosion performance test was carried out using the weight loss method. The detailed test conditions and solution medium composition are shown in Table 27, and the test results are listed in Table 28.

[0187] Table 26 Anti-CO of Comparative Examples 1 to 5 2 Corrosion performance test conditions

[0188]

[0189] Table 27 Test conditions for corrosion resistance of acid fracturing fluids in comparative examples 1 to 5

[0190] Medium (fresh acid) 10% HCl+1.5% HF+3% HAc+5.1% high temperature acidification corrosion inhibitor Temperature(℃) 140 Dosage <![CDATA[≥20ml / cm 2 ]]> Test time (h) 6 Total pressure(MPa) 10 .

[0191] Table 28 Corrosion resistance of comparative examples 1 to 5

[0192] Serial number <![CDATA[Simulated CO 2 Corrosion rate (mm / a) under corrosive medium]]> Corrosion rate in simulated acid fracturing corrosive medium (mm / a) 1 0.0053 7.0358 2 0.0046 6.7239 3 0.2987 18.8893 4 0.0018 59.8746 5 0.1602 13.5527 .

[0193] The high strength CO resistant 2 The stainless steel alloy oil casing samples in Examples 1 to 11 and Comparative Examples 1 to 5 were sampled for CO resistant tests. The test results are shown in Tables 11 to 13 and 22 to 24. 2 Corrosion performance test, detailed test conditions and solution medium composition are shown in Table 15 and Table 26, and the test results are listed in Table 17 and Table 28. The weight loss method was used to test the corrosion resistance of the stainless steel oil casing in Examples 1 to 11 and Comparative Examples 1 to 5. The detailed test conditions and solution medium composition are shown in Table 16 and Table 27, and the test results are listed in Table 17 and Table 28.

[0194] It can be seen from Tables 12 to 14 and Tables 23 to 25 that the high strength CO resistant 2 The corrosion-resistant stainless steel alloy oil casing has high strength and good impact toughness, and its strength level reaches 52-135KSI. By comparing the mechanical properties of Examples 1 to 11 and Comparative Examples 1 to 2, it can be found that the N content has a very significant effect on the strengthening of the mechanical properties of the material during the cold deformation process of the material. When the N content is less than 0.05, the material cannot be strengthened to 110KSI with the same deformation; and when the N content is greater than 0.3, the material strength exceeds 140KSI with the same deformation. 2 In the corrosion performance test, the corrosion rates of Examples 1 to 11 are lower than those of Comparative Examples 3 and 5, and are equivalent to the corrosion rate of Comparative Example 4. By comparing Example 1 with Comparative Examples 1 to 2, it can be found that the N content has an important effect on the material's resistance to CO. 2 The higher the N content, the better the material's resistance to CO 2 The better the corrosion performance. In the test of the corrosion resistance of acid fracturing fluid, compared with Comparative Examples 3 to 5, Examples 1-11 showed a better corrosion rate. Therefore, compared with Comparative Examples 3 to 5, the corrosion resistance of Examples 1-11 is better. Similarly, by comparing Example 1 with Comparative Examples 1 to 2, it can be found that the higher the N content, the better the corrosion resistance of the material to acid fracturing fluid.

Claims

1. A high-strength CO2 corrosion-resistant stainless steel, characterized in that: The stainless steel comprises, by weight percentage, 0.076% C, 0.18% Si, 4.72% Mn, 24.9% Cr, 18.8% Ni, 4.32% Mo, 0.091% Al, 0.33% Cu, 0.14% Co, 0.87% W, 0.16% N, 0.098% Re, and the remainder is Fe and other unavoidable impurities. The composition satisfies the following conditions: Creq / Nieq is 1.4, and PREN is 43.2, wherein Nieq is nickel equivalent, Creq is chromium equivalent, and PREN is pitting equivalent; Prepared by the following method: (1) Smelting: According to the above formula, molten steel is obtained by adopting the AOD or AOD+ESR smelting process; (2) Making a tube blank: subjecting the molten steel obtained in step (1) to die casting, followed by hot forging to obtain a tube blank for extrusion, or subjecting the molten steel obtained in step (1) to continuous casting, followed by hot rolling to obtain a tube blank for perforation; (3) Heating pipe making: hot extrusion or hot perforation treatment is performed on the tube blank in step (2) to make a seamless rough tube; (4) Heat treatment: subjecting the rough pipe in step (3) to solid solution heat treatment to obtain a rough pipe in a solid solution state extruded or perforated state; (5) Cold rolling: The solid solution extruded or perforated rough pipe in step (4) is subjected to cold deformation to form a pipe with the required specifications and strength; the processed rough pipe is cold rolled to reduce the pipe specification from Φ152*25mm to Φ127*15mm, degreased and annealed at 1000°C for 25 minutes, pickled and straightened; then the intermediate pipe is subjected to final cold rolling to reduce the pipe specification from Φ127*15mm to Φ88.9*7.34mm, and after finishing, a 135KSI high-strength CO2 corrosion-resistant stainless steel alloy pipe is obtained; The forging ratio in the hot forging process in step (2) is 3.0; The extrusion or perforation temperature during the hot extrusion or hot perforation treatment in step (3) is 1180°C; In the step (3), when hot extrusion or hot piercing is performed, the tube blank is first preheated to 900°C for 1 hour to completely austenitize the alloy, and then heated to the extrusion or piercing temperature; The solution heat treatment temperature in step (4) is 1000°C.

2. The high-strength CO2 corrosion-resistant stainless steel according to claim 1, characterized in that: In terms of weight percentage, the stainless steel composition also includes at least one of: 0<Nb≤0.1%, 0<V≤0.1%, and 0<Ti≤0.1%.

3. A high-strength CO2 corrosion-resistant stainless steel oil casing, characterized in that: The stainless steel is obtained by the stainless steel as claimed in any one of claims 1 or 2.

4. Application of the high-strength CO2 corrosion-resistant stainless steel oil casing as described in claim 3 in the field of oil and natural gas extraction.

Citation Information

Patent Citations

  • High strength anticorrosion stainless steel, stainless steel oil casing and manufacturing method thereof

    CN104846291A

  • Anti-corrosion stainless steel, oil casing and manufacturing method thereof

    CN106555134A

  • S32750 Austenitic Ferrite Super Duplex Stainless Steel Seamless Pipe for Deep Sea Manifold and Method for Preparing Same

    US20230167520A1